Sosialisasi Keamanan Manusia Terhadap Perlindungan Konsumen Dari Bahaya Makanan Dan Minuman Yang Telah Melewati Masa Kelayakan Konsumsi (Kegiatan Di Kelurahan Dalam Bugis Kecamatan Pontianak Timur) - Elyta, Elyta (Universitas Tanjungpura, 2018)
Human security concerns complex activities, one of which is in the trade sector that involves business actors, consumers and commodities. The government seeks measures to safeguard human security. This activity focuses on human security that seeks to be realized through the dissemination of human security to consumer protection from the dangers of food and beverages that have passed the consumption feasibility period (activities in urban neighborhoods in East Pontianak sub-districts), namely consumer protection from excessive food and beverages. Business actors who threaten the human security of consumers by selling food and beverages in excess can be subject to regular reprimand sanctions until they are imprisoned for a minimum of 5 years and a fine of Rp.2 billion.